Allelopathic activity of picocyanobacterium Synechococcus sp. on filamentous cyanobacteria - Śliwińska-Wilczewska S. (2017)
Allelopathy of picocyanobacterium Synechococcus sp. may be involved in the formation of massive blooms and their subsequent global expansion in many aquatic ecosystems. However, the effect of the allelopathic activity of this species on filamentous cyanobacteria remains unknown. In this study, we tested the allelopathic activity of Synechococcus sp. on growth, pigment content and chlorophyll fluorescence of filamentous cyanobacteria Aphanizomenon flos-aquae, Nostoc sp., Phormidium sp. and Rivularia sp. by single and repeated addition of cell-free filtrate. Negative effects against Nostoc sp. and Phormidium sp. were amplified by repeated filtrate additions compared with single filtrate addition. A maximum reduction in growth and a maximum quantum yield of photosystem II (PSII) photochemistry (Fv/Fm) relative to controls were observed for Phormidium sp. However, the addition of picocyanobacterial filtrate stimulated the growth and Fv/Fm of A. flos-aquae. Synechococcus sp. filtrate had no allelopathic effects on the growth and Fv/Fm of Rivularia sp. Moreover, filtrates caused significant decreases in the chlorophyll a (Chl a) contents of Phormidium sp. and Rivularia sp. cells. The addition of filtrate also resulted in increased cell carotenoid (Car) content in A. flos-aquae and Nostoc sp. These results showed for the first time that picocyanobacterium Synechococcus sp. negatively and positively affected coexisting filamentous cyanobacteria. © 2017 Elsevier